Sleep quality and anxiety level in employees - TEKER SAYIN, AYŞE GÜLSEN; LÜLECİ, NİMET EMEL (KARE PUBL, 2017)
OBJECTIVE: The aim of this study was to measure the sleep quality and anxiety level of a group of employees, as well as determine the relationship between sleep quality and anxiety and other factors. METHODS: A total of 130 of 185 employees at a university campus were enrolled in this cross-sectional study. A descriptive questionnaire, the Pittsburgh Sleep Quality Index, and the Beck Anxiety Inventory were the data collection instruments. In addition to univariate analysis, the relationship between the 2 scales was examined with Spearman correlation analysis. RESULTS: Of the participants, 38.9% had poor sleep quality. Gender, income level, presence of a chronic disease, regular medication use, and relationship with family and the social environment were found to affect both sleep quality and anxiety. A decrease in sleep quality was associated with an increase in the level of anxiety. CONCLUSION: Poor sleep quality and a high anxiety level are common in this country, as in the rest of the world. Socioeconomic interventions and psychosocial support to improve the status of individuals with risk factors, such as chronic disease, will reduce anxiety and improve sleep quality and overall psychosocial health. Further prospective studies should be conducted with different groups of participants and with larger samples to expand knowledge of the relationship between sleep quality and anxiety.
Keywords: Anxiety; anxiety disorders; occupational health; public health; sleep; sleep-wake disorders; PRIMARY-CARE; INSOMNIA; DISORDERS; EPIDEMIOLOGY; DISTURBANCE